The Failure of New Political Parties and ID Figures: Nobility of Technocrats in Analysis of Voting Behavior in Jambi - Hatta Abdi Muhammad; Nopyandri Nopyandri (Universitas Medan Area, 2021)
This study aims at analyzing the failure of the Perindo Party, PSI, Garuda Party, and Berkarya Party as new political parties in the 2019 election contestation in Jambi Province. This study was a qualitative descriptive study and data were obtained through observation, interviews, and archival records. After the data was collected, the data were analyzed using interactive model analysis. The results of this study showed that the failure of these four new political parties in Jambi Province was related to the absence of figures that were widely known to the public. The characteristics of local politics which were affected by emotional and primordial ties made political parties adopt the technocrat aristocratic pattern to maintain their existence in the political arena in Jambi Province. The success of political parties in Jambi Province was closely related to public voting behavior that was influenced by the presence of figures with technocrat backgrounds in large parties. It was proven by the existence of old parties because they had famous figures from former officials or state apparatus as well as families of public officials such as Hasan Basri Agus (Golkar), and Nurdin Hamzah family (PAN).